Heat Transfer Enhancement in Nanofluid Flows Augmented by Magnetic Flux - Arjun, Kozhikkatil Sunil; Kumar, Rakesh (UI Scholars Hub, 2023)
Heat transfer enhancement could be realized using magnetohydrodynamics together with nanofluids specifically in flow micro-convection in a microtube, flow past a vertical porous plate, and square duct flow with discrete heat sources numerically. A critical value for the Rayleigh number, a maximum value for the magnetic field strength, a low Reynolds number, and volume concentrations exists for thermal enhancement to simulate nanofluid flow in a microtube. Heat transfer enhancement is observed with a reduction in the magnetic field strength in a flow past a heated porous vertical plate. Alumina nanofluid subjected to Hartmann number 10 can boost 81% enhancement in Nusselt number in a square duct at lower Reynolds number using three discrete heat sources under the impact of thermal and solutal buoyancy. A 4% increase in the cooling effect near the center of the last heat source in a nanofluid flow is of practical use in hot spot cooling.